Menstrual care for individuals with disability: a case report - Nadia Abdul Bari,; Leelavathi Muthupalaniappen,; Noor Azimah M, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Individuals with disabilities have different needs and concerns at different stages of life. The arrival of puberty brings about new challenges especially for females with issues related to menstrual care involving both the patient and their caregivers. This case report is about a 13-year-old girl with Down syndrome who was cared for by her widowed father since the age of six. She was suffering from severe mental disability. Her father was concerned, because she was unable to maintain personal hygiene during menses such as changing sanitary napkins and managing stains, hence requested for menstrual manipulation. Options for menstrual manipulation for individuals with disabilities include both medical and surgical interventions. Hormonal therapy options include oral contraceptive pills, depo-provera, progestin implants and progesterone release intra-uterine contraceptive devices. Surgical options such as hysterectomy or endometrial ablation may be considered as a last resort as it is more invasive and irreversible, involving ethical and legal implications. Selection of the suitable therapy involves shared decision making between health care provider and caregiver taking into consideration the patient’s best interest. This case report also highlights the role of family physicians in managing and coordinating care on delicate issues related to menstrual care for people with disabilities. This case report may serve as a guide to physicians and families with special needs children, while approaching issues on menstrual care.